Avelsarbete med mjölkproducerande getter – fokus på Norge och Frankrike - Andersson, Julia (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2012)
The main part of the goats in the world is located in developing countries, whereas active breeding programs are mainly restricted to Northern America and Europe. Goat milk can be processed to several products and goat cheese is the main product. An organized breeding program is carried out in France and Norway but is not present in Sweden. Important selection traits for milk producing goats include milk, protein and fat yield along with protein and fat content. Functional traits have been more important the past years and they have large economic importance for the farmers. Seasonally reproduction has been observed in goats from temperate areas. Ovulation is stimulated by using light treatments, hormonal treatments or introduction of bucks.